Understanding Balanced Nutrition Knowledge among Elementary School Children in Rural Sampang: Implications for Nutrition Education Interventions - Rosana Wulandari, Agustin; Dian Rosanti, Nadia; Asyura, Renidya (Journal of Nutrition and Public Health, 2025)
Background: Balanced nutrition is an important factor in supporting the growth and development of elementary school children. However, national data shows that the prevalence of stunting and double nutrition problems in Indonesian children remains high. This condition is exacerbated by students' low understanding of the concept of balanced nutrition, which has the potential to affect their eating patterns and health. Aims: This study aims to describe the level of balanced nutrition knowledge among fifth and sixth grade students at SDN Karang Dalem 1 Sampang as a basis for developing more targeted nutrition education strategies. Methods; This study used a descriptive design with a population of 80 fifth and sixth grade students. The sampling technique used total sampling. Data were collected through a questionnaire containing 20 true-false questions that had been modified from previous studies. Data analysis was performed using frequency distribution and percentages. Result; The results showed that the majority of respondents were female (61%) and aged 11 years (69%). The level of balanced nutrition knowledge was mostly in the adequate category (53%), while 39% of students had good knowledge, and the remaining 9% were classified as lacking. Conclusion; The balanced nutrition knowledge of fifth and sixth graders at SDN Karang Dalem 1 Sampang was mostly in the adequate category. These findings emphasize the need for more innovative nutrition education interventions, such as animated media or project-based learning methods, to improve students' understanding and support efforts to prevent double nutrition problems in elementary school children.